Inhibitory effects of fluoxetine on photosensitive retinal ganglion cells - Hughes, S; Foster, R; Peirson, S; Hankins, M (Investigative Ophthalmology and Visual Science, 2016)
Purpose : Selective serotonin reuptake inhibitors (SSRIs) such as fluoxetine (Prozac) are widely used for the treatment of depression. Common side effects of fluoxetine include blurred vision and increased pupil dilation, often leading to angle-closure glaucoma. However, the mechanisms underlying the effects of fluoxetine on visual function and pupil constriction are not well understood. Photosensitive retinal ganglion cells (pRGCs) play a pivotal role in controlling levels of pupil constriction. We have therefore investigated the effect of fluoxetine and other classes of antidepressants on pRGC function and melanopsin driven light responses. Methods : Multi-electrode array (MEA) recordings were performed on retina explants from rd1 mice lacking rods and cones, before and after the application of antidepressant drugs. Retina were maintained at 34oC, and perfused with AMES media bubbled with 95% O2, 5% CO2. Melanopsin driven light responses were measured as changes in spike firing rate following stimulation with 480nm light. Results : Fluoxetine suppresses spontaneous spike firing and reduces the duration of pRGC light responses in a dose dependant manner, leading to a complete loss of melanopsin driven responses. The tricyclic antidepressant Clomipramine mimics the effect of fluoxetine, yet application of serotonin itself, or application of Citalopram, a potent and highly selective SSRI that exerts lesser effects on noradrenalin and dopamine uptake compared to fluoxetine, have only minimal effects on pRGC function. These data suggest that the effects of fluoxetine may not be dependent on serotonin, but rather due to off-target effects on other neurotransmitters. Fluoxetine also directly inhibits TREK-1 ion channels, which are expressed by pRGCs. The small molecule inhibitor of TREK-1, Spadin, was found to suppress spike firing and reduced the magnitude of pRGC light responses elicited to bright light stimuli, but did not fully replicate the effects of fluoxetine. Conclusions : Our data show a direct effect of SSRI’s and other classes of antidepressants on retina function and melanopsin expressing pRGCs. Our data suggest that fluoxetine may regulate pRGC function by multiple mechanisms, likely involving dopamine, cAMP and TREK-1 ion channels. These data offer a possible mechanism to explain the side effects of fluoxetine on pupil dilation and resulting susceptibility to angle-closure glaucoma.